Research on Watershed Management with Special Reference to the Estimation of Useful Life of Reservoir - Guha, D P (Journal of Soil and Water Conservation, 2022)
Sedimentation of reservoirs and assurance of prolonged water supply from their catchments in a river valley project are a worry to an Engineer and a problem to the Soil Conservationists. In U.S.A., it is reported that two thousand million dollars have so far been invested over the construction of 8,400 dams and a recent sample survey revealed that only 17 per cent of them are supposed to remain useful over 200 years and 38 per cent are threatened by complete sedimentation within 50 years.In India, 135 irrigation and hydel projects were proposed in the first five year plan. Unless the nature and intensity of runoff and erosional problems of each and every indivi- dual projects are properly assessed, funds for soil conservation works on the respective catchments can never be justifiably recommended.In some of the projects, fortunately, it has been possible to make the assessment through actual hydrological studies before the con- struction of the reservoirs could be under- takeh. But in most cases it was a guess work. Estimation of sedimentation and water yield in a project is necessary both for planning the reservoir and also for planning the soil conservation works on its catchment.